Progress in Ultrafast Intense Laser Science Volume IX - Yamanouchi, Kaoru; Midorikawa, Katsumi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The PUILS series delivers up-to-date reviews of progress in Ultrafast Intense Laser Science, a newly emerging interdisciplinary research field spanning atomic and molecular physics, molecular science, and optical science, which has been stimulated by the recent developments in ultrafast laser technologies. Each volume compiles peer-reviewed articles authored by researchers at the forefront of each their own subfields of UILS. Every chapter opens with an overview of the topics to be discussed, so that researchers unfamiliar to the subfield, as well as graduate students, can grasp the importance and attractions of the research topic at hand; these are followed by reports of cutting-edge discoveries. This ninth volume covers a broad range of topics from this interdisciplinary research field, focusing on ultrafast molecular responses to an intense laser field, advanced techniques for attosecond pulse generation, atomic and molecular responses to attosecond pulses, photoelectron spectroscopy of atoms and molecules interacting with intense light fields, and attosecond pulse interaction with solid materials.
From the Contents: Trajectory-Based Coulomb-Corrected Strong Field Approximation -- The Role of Nuclear vibrational Motion in Molecular High Harmonic Generation in a Mid-infrared Laser Field -- Attosecond Dynamics of Coherent Electron-Nuclear Wave Packets in Molecules -- Gating Techniques for Shaping of Attosecond Pulses -- Transform-limited Attosecond Pulse Generation through Atto-chirp Compensation by Material Dispersion -- Carrier-Envelope Phase Stabilization.
Keywords: Physics; Chemistry, Physical organic; Physics; Laser Technology, Photonics; Physical Chemistry; Optics and Electrodynamics; Applied and Technical Physics